Vaginal Microbiota and Cytokine Levels Predict Preterm Delivery in Asian Women - Kumar, Manoj; Murugesan, Selvasankar; Singh, Parul; Saadaoui, Marwa; Elhag, Duaa Ahmed; Terranegra, Annalisa; Kabeer, Basirudeen Syed Ahamed; Marr, Alexandra K.; Kino, Tomoshige; Brummaier, Tobias; McGready, Rose; Nosten, François; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Preterm birth (PTB) is the most common cause of neonatal morbidity and mortality worldwide. Approximately half of PTBs is linked with microbial etiologies, including pathologic changes to the vaginal microbiota, which vary according to ethnicity. Globally more than 50% of PTBs occur in Asia, but studies of the vaginal microbiome and its association with pregnancy outcomes in Asian women are lacking. This study aimed to longitudinally analyzed the vaginal microbiome and cytokine environment of 18 Karen and Burman pregnant women who delivered preterm and 36 matched controls delivering at full term. Using 16S ribosomal RNA gene sequencing we identified a predictive vaginal microbiota signature for PTB that was detectable as early as the first trimester of pregnancy, characterized by higher levels of Prevotella buccalis, and lower levels of Lactobacillus crispatus and Finegoldia, accompanied by decreased levels of cytokines including IFNγ, IL-4 and TNFα. Differences in the vaginal microbial diversity and local vaginal immune environment were associated with greater risk of preterm birth. Our findings highlight new opportunities to predict PTB in Asian women in low-resource settings who are at highest risk of adverse outcomes from unexpected PTB, as well as in Burman/Karen ethnic minority groups in high-resource regions.